Numerical Simulation of Soil Displacement and Settlement in Deep Foundation Pit Excavations Near Water - Zhongjing Hu; Qingbiao Wang; Shuo Yang; Zhenyue Shi; Bo Liu; Hongxu Song; Fuqiang Wang (Geofluids)
Advancing urbanization in China requires large-scale high-rise construction and underground transportation projects. Consequently, there is an increasing number of deep foundation pits adjacent to water bodies, and accidents occur frequently. This study uses a numerical simulation method to study the stability of the deep foundation pit near water based on the Biot three-dimensional seepage-stress coupling model, with the open-cut section on the south bank of the Jinan Yellow River Tunnel Project as the engineering field test. This indicates the following: (1) the maximum horizontal displacement of the diaphragm wall occurred in the fifth excavation stage, and a horizontal brace effectively controlled the inward horizontal displacement of the foundation pit; (2) considering the effect of seepage in the soft soil foundation, the maximum vertical displacement of the ground surface at each excavation stage occurred adjacent to the underground continuous wall. As the depth of the foundation pit increased, the vertical surface settlement decreases gradually in the direction away from the excavation face; (3) considering the seepage conditions, within each interval of excavation of the foundation pit, the horizontal displacement of the continuous underground wall and ground settlement declined; and (4) the numerical simulation and field monitoring data were in good agreement. Under the conditions of accurate model simplification and parameter selection, numerical simulations can adequately forecast conditions of the actual project.